Editorial: Reason after All - Pasierbek, Wit (Horyzonty Wychowania, 2015)
The characteristics of reason (Latin ratio) and reason in general, so much essential in man’s rational existence, have been examined for a long time. Ancient Greeks thought that reason is a reflective ability, which concentrates on some subject in order to get to know it. Eventually developing this notion theoretically in philosophy and religion, they indicated that reason is an instrument of thinking, which understands the world and man’s existence and learns, coordinates and has control over everything. Plato ascribed divine power, which rules the world, to reason; whereas Aristotle, differentiating between theoretical and practical reason, claimed that reason is characterized by immortality and divinity...